2023
DOI: 10.1002/tqem.22005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface water quality near municipal Solid Waste dumping facility in Bukoba, Kagera Region, Tanzania

Abstract: Water samples were collected from River Kanoni which passes near a municipal solid waste (MSW) dumping facility in Bukoba Town, Kagera Region, United Republic of Tanzania. The objective of the study was to assess surface water pollution caused by a MSW dump. Selected physico‐chemical parameters (pH, temperature, Electrical Conductivity [EC], and Total Dissolved Solids [TDS]), nutrient levels, as well as heavy metals concentrations (Pb, Zn, Cu, Cr, Cd) were analyzed in the laboratory at the University of Dar es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Studies carried out on the River Rwizi showed pH ranging from 5.9 to 6.9, and this was attributed to the hydrolysis of cations, acidic gases dissolved in water and decomposition of organic matter in the river water [34]. Lema and Mwegoha [35] and Sikuku [36] reported higher pH values of 7.75-8.82 for the Kanoni River (Tanzania) and 7.32 to 8.24 for Kenyan rivers: Hippo Point, Kisat, Mbogo, Nzoia, Nyando, Woroya and Yala. The pH values obtained in the Kagera River in this study are lower than the 7.96-8.22, 6.2-8.0, 6.6-7.5, 5.85-7.60 and 8.05-8.30 reported for water from the Nyabugogo and Nyabarongo rivers, Rwanda [37]; Mohokare River (Lesotho) [38]; and the River Aturukuku [39], River Nyamugasani [40] and River Rwimi of Uganda [33,40], but comparable to 5.60-7.40 and 5.58-6.80 for the River Nyamwamba and River Mubuku of Uganda [33,41].…”
Section: Phmentioning
confidence: 99%
“…Studies carried out on the River Rwizi showed pH ranging from 5.9 to 6.9, and this was attributed to the hydrolysis of cations, acidic gases dissolved in water and decomposition of organic matter in the river water [34]. Lema and Mwegoha [35] and Sikuku [36] reported higher pH values of 7.75-8.82 for the Kanoni River (Tanzania) and 7.32 to 8.24 for Kenyan rivers: Hippo Point, Kisat, Mbogo, Nzoia, Nyando, Woroya and Yala. The pH values obtained in the Kagera River in this study are lower than the 7.96-8.22, 6.2-8.0, 6.6-7.5, 5.85-7.60 and 8.05-8.30 reported for water from the Nyabugogo and Nyabarongo rivers, Rwanda [37]; Mohokare River (Lesotho) [38]; and the River Aturukuku [39], River Nyamugasani [40] and River Rwimi of Uganda [33,40], but comparable to 5.60-7.40 and 5.58-6.80 for the River Nyamwamba and River Mubuku of Uganda [33,41].…”
Section: Phmentioning
confidence: 99%